Digest: Disentangled bank: Less diverse urban environments modify the shape and magnitude of natural selection. (5th September 2018) - Hood, Glen R.; Zhang, Linyi; Egan, Scott P.
Abstract: Urbanization provides a natural experiment for biologists to test how anthropogenic environmental change affects evolution in real time and frames predictions for anticipated evolutionary outcomes worldwide. Start et al. (2018 ) found that changes in species interactions (herbivore abundance and avian predation) along urbanization gradients predictably alter the shape and magnitude of natural selection on gall size (a defensive trait), suggesting that rapid global environmental change can alter species interactions, which may have foreseeable evolutionary consequences.